RISK FACTORS OF LATENT TUBERCULOSIS INFECTION IN HEALTHCARE WORKERS AT HOSPITALS IN JEMBER CITY INDONESIA - Wardani, Hamidah Retno; Mertaniasih, Ni Made; Soedarsono, Soedarsono (African Journal of Infectious Diseases (AJID), 2020)
Background: Healthcare workers in Tuberculosis (TB) and non-TB units in hospitals have a high risk of experiencing Latent Tuberculosis Infection (LTBI), because of exposure to droplets containing Mycobacterium tuberculosis. This study aims to prove LTBI incidence and risk factors to healthcare workers at the hospital in Jember City. Material and Methods: a cross-sectional study, from January to March 2020 in two hospitals in Jember City. Healthcare workers in the TB care and non-TB care unit were examined using Tuberculin skin test (TST) with a cut off ≥ 10 mm for positive LTBI. Chest x-ray and clinical examination to rule out active TB and a standardized questionnaire were also used. Results: 128 healthcare workers completed the questionnaires, clinical, tuberculin skin test (TST), and chest x-ray data. LTBI incidence of positive results 61.7% (n = 79). Contacts TB in the workplace (p value = 0.219; OR = 1.643; CI = 0.742-3.641) and a unit of work (p value = 0.102; OR = 0.760; CI = 0.559-1.031) has no relationship with LTBI. The profession (p value = 0.020; OR = 1.112; CI = 0.896-1.403), the duration of the work (p value = 0.039; OR = 2.984; CI = 1.067-8.342), and BCG immunization (p value =0.000; OR = 0.151; CI = 0.052-0.438) have important relationships with LTBI. Conclusion: TB infection with a high incidence, a risk of transmission to healthcare workers, and a relationship between occupational risk factors and LTBI among healthcare workers in Jember City, Indonesia have been established in this study.